Faktor Penyebab dan Penanganan Kenakalan Remaja di SMK 10 November Tambun Selatan - Yuliana Putri; Putri Wulandari; Siti Aisyah; Eliza Agustina; Tugimin Supriyadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The phenomenon of student brawls at SMK 10 November Tambun Selatan is a serious problem that has a negative impact on physical, emotional, social, and material. This study aims to analyze the factors that cause and solve juvenile delinquency, especially brawls. Using descriptive qualitative method with purposive sampling technique, data were collected through interviews and observations of counseling guidance teachers and students involved. Data analysis followed the Miles and Huberman model. The results showed three main factors causing brawls: psychological factors (self-esteem and motivation), social factors (group pressure), and subcultural factors (peer group influence). Handling includes identification and evaluation, communication, coaching, education, and punishment. These measures, which involve cooperation between the school, parents and students, are expected to reduce cases of brawls and restore order in the school and community.